2022
DOI: 10.1136/annrheumdis-2022-222199
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine prophylaxis is associated with fewer gout flares after COVID-19 vaccination

Abstract: ObjectivesCOVID-19 vaccination often triggers a constellation of transitory inflammatory symptoms. Gout is associated with several comorbidities linked to poor outcomes in COVID-19, and gout flares can be triggered by some vaccinations. We analysed the risk of gout flares in the first 3 months after COVID-19 vaccination with inactivated virus, and whether colchicine can prevent gout flares following post-COVID-19 vaccination.MethodsA clinical delivery population-based cross-sectional study was conducted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
(17 reference statements)
1
15
0
1
Order By: Relevance
“…Recently, a cross-sectional study reported that inactivated COVID-19 vaccination was associated with a 6-fold higher odds of gout flares [9] . The inactivated COVID-19 vaccine in that study contains aluminum hydroxide adjuvant, and previous studies have shown that adjuvant could activate the inflammatory cascade, resulting in an increased risk of gout flares [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a cross-sectional study reported that inactivated COVID-19 vaccination was associated with a 6-fold higher odds of gout flares [9] . The inactivated COVID-19 vaccine in that study contains aluminum hydroxide adjuvant, and previous studies have shown that adjuvant could activate the inflammatory cascade, resulting in an increased risk of gout flares [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have prompted the implementation of an enhanced post-marketing surveillance program for gout flares following vaccination [8] . Recently, a study showed that the odds of gout flares increased by almost 6-fold after receiving the inactivated COVID-19 vaccines [9] . However, whether the risk of gout flares increases after receiving other COVID-19 vaccines, such as messenger RNA (mRNA) vaccines BNT162b2 (Pfizer–BioNtech, hereafter referred to as BNT) or adenovirus vector vaccines ChAdOx1 nCov-19 (Oxford–AstraZeneca; hereafter referred to as ChAd) is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal menstrual cycles (delayed menstruation or increased bleeding or pain) [106], anaphylaxis [44], gout flares [48], lymphadenopathy [107,108], rhabdomyolysis [109], shoulder injuries related to vaccine administration (SIRVA) [109,110], and Vogt-Koyanagi-Harada syndrome [19] have also been reported following COVID-19 vaccination (Table 1). SIRVA is an acute inflammation of the shoulder that causes substantial shoulder pain and a limited range of motion [109,110].…”
Section: Othersmentioning
confidence: 99%
“…NLRP3 inflammasome is associated with IL-1β secretion. Colchicine has the effect of suppressing the formation of NLRP3 inflammasome [47], which may be useful for vaccine-associated inflammation [48]. The mRNA vaccines increase both immunostimulatory cytokines release and inflammatory cytokines release, especially after the second vaccination and in patients infected by SARS-CoV-2 [10].…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation